ANALISIS KETERAMPILAN BERBICARA SISWA KELAS IV SD NEGERI 0306 SOSOPAN T.A. 2025/2026 - Putri Miftahul Jannah; Dody Feliks Pandimun Ambarita; Eva Betty Simanjuntak; Halimatusakdiah; Faisal; Charles Fransiscus Ambarita (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the speaking skills of fourth-grade students at SD Negeri 0306 Sosopan in the 2025/2026 academic year. This is a descriptive study with a qualitative approach. The subjects were 22 fourth-grade students. The instruments used were tests and a research rubric. The results show that the speaking skills of fourth-grade students at SD Negeri 0306 Sosopan are predominantly in the sufficient category, with scores on five aspects of speaking skills: pronunciation (50%), intonation (54%), fluency (54%), language and content (64%), and expression (64%).